Building Scientific Knowledge in English: Integrating Content, Cognition and Communication in Secondary School CLIL Biology - Pilar Gerns (National Research University Higher School of Economics, 2023)
Background: The focus of this paper is on Dalton-Puffer's construct of the Cognitive Discourse Function (cdf) (2013), which offers clil teachers a practical framework through which they can more easily understand the complex idea of integrating the content, cognition, and language required for their subject. These functions have mainly been addressed from classroom observations or task prompts, and little is known about their teachability and effectiveness on students' content knowledge. Purpose: This paper explores whether the cdf of 'comparing' (a subcategory of 'classify') can be taught to Spanish seventh-grade clil biology students (N = 37) and examines the effect of teaching it explicitly on their written performance. Method: An operational framework was developed to define this cdf and an exploratory study was performed in which students were asked to hand in written comparisons. Quantitative and qualitative pre-and post-tests were applied. Results: Significant results were obtained for the experimental groups, which improved in both content and language learning, scoring higher on inclusion of content points, justification of their scientific claims, concept formation and use of lexico-grammatical forms. Conclusion: These findings add to our understanding of the importance of integrating cognition and language in teaching and learning natural sciences, within which CDFs can be a useful starting point.